TREE MOTIFS USED IN OTTOMAN TILES AND CERAMICS - KILIÇASLAN, Merve; BORATAV, Olcay (SSD Journal, 2025)
The tree culture stands out as a common cultural element in world societies. In ancient Turkish epics, the tree motif, shaped by the influence of Central Asian Shamanism, guided Turkish art and gained symbolic meanings in mythology. The Tree of Life, symbolizing the earth with its roots and the sky with its trunk and branches, was considered sacred in creation myths. In Turkish communities, the Tree of Life was regarded as a sacred entity before Islam, and after the adoption of Islam, it continued to be used as a motif in works of art. During the period from the Seljuk era to the Ottoman Empire, this motif was depicted on tiles and ceramics alongside naturalistic flowers such as tulips, roses, and hyacinths. These motifs facilitated cultural transmission between generations and underwent periodic stylistic transformations. In the 16th and 17th centuries, magnificent examples of the Tree of Life motif can be found in significant structures such as Topkapı Palace and the Eyüp Sultan Tomb. The Tree of Life has held a profound place in Turkish art as a universal cultural element symbolizing the connection between the world and humanity. By examining the historical and symbolic processes of tree motifs, their use in different periods has been compared. The Tree of Life was a significant motif during the Seljuk and Ottoman periods, becoming more pronounced in the Ottoman era with the Karamemi style. The cypress tree was featured in depictions of immortality and paradise, while motifs of pomegranates, grapes, and vines symbolized abundance and prosperity in works of art. The pomegranate and grape motifs can be seen as striking decorative elements in structures such as Rüstem Pasha Mosque, Sultanahmet Mosque, and the Tiled Kiosk, surviving to the present day. Today, tree motifs continue to exist in both classical and modern designs through the underglaze technique. This study aims to contribute to cultural heritage by analyzing tree motifs through the relationship between belief and symbolism.